2004
DOI: 10.1038/ni1135
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a conserved Il4 silencer impairs T helper type 1–mediated immunity

Abstract: Helper T cell differentiation involves silencing as well as activation of gene expression. We have identified a conserved silencer of the gene encoding interleukin 4 (Il4) marked by DNase I hypersensitivity (HS IV) and permissive chromatin structure in all helper T cells. Deletion of HS IV increased Il4 and Il13 transcription by naive T cells and led to T helper type 2 skewing in vitro. HS IV controlled Il4 silencing during T helper type 1 differentiation, as HS IV-deficient T helper type 1 cells that expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
127
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 48 publications
1
127
0
Order By: Relevance
“…T cell isolation, retroviral transduction, and differentiation were performed as described previously (43). A more detailed description is included in the SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…T cell isolation, retroviral transduction, and differentiation were performed as described previously (43). A more detailed description is included in the SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin remodeling and enhancement of transcription of a gene are regulated by trans-acting factors that bind to specific DNA regulatory elements. Many laboratories including ours have shown that the Th2 cytokine locus is regulated by a number of regulatory elements including enhancers [CNS-1/ HSS (9, 20-22), CNS-2/HSV (20, 23), IE/HSII (20)], a silencer (HSIV) (20,24), and a locus control region (LCR) (25).We have shown previously that the expression of Th2 cytokines is coordinately regulated by the Th2 LCR that is located in the 3′ region of the rad50 gene (25). The Th2 LCR is composed of four DNase I-hypersensitive sites, namely RHS4, RHS5, RHS6, and RHS7 (13, 26).…”
mentioning
confidence: 99%
“…Chromatin remodeling and enhancement of transcription of a gene are regulated by trans-acting factors that bind to specific DNA regulatory elements. Many laboratories including ours have shown that the Th2 cytokine locus is regulated by a number of regulatory elements including enhancers [CNS-1/ HSS (9, 20-22), CNS-2/HSV (20, 23), IE/HSII (20)], a silencer (HSIV) (20,24), and a locus control region (LCR) (25).…”
mentioning
confidence: 99%
“…Likewise, the mechanisms responsible for locking in the activity or silencing of cytokine genes during helper T cell maturation are still incompletely defined. We do not yet know whether the stability we observe is truly epigenetic, maintained by self-propagating chromatin marks, or is more accurately genetic, maintained by trans-activators other than T-bet, Hlx, or GATA-3, and conventional repressors acting at negative cis-elements (32). In either case, it is remarkable, although not fully explicable, that recruitment of an engrailed repression domain has such a minor effect on cytokine expression in mature cells.…”
Section: Discussionmentioning
confidence: 92%